Laporan Kelompok Praktik Pengalaman Lapangan (PPL) Fakultas Keguruan Ilmu Pendidikan (FKIP) Unitomo di SMK PGRI 13 Surabaya - Sabilatus Tsaniah; Alberta Asmari; Zulaiha Rumaf; Anatasya Benny Pratama; Alfian Akbar Fajar Sidiq; Maria Evriana Priska Murni; Hikmah Maulida Fitriana; Patricia Angelica Ira; Alfiana Sri Wahyu Wulandari; Sumarton Sumarton; Salman Alfarizi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The Field Experience Practice Program (PPL) at SMK PGRI 13 Surabaya is designed to equip students from the Faculty of Teacher Training and Education at Dr. Soetomo University with direct experience in the world of education. This activity provides students with the opportunity to apply the theories learned in lectures to real-life situations, enhance their teaching skills, and understand the challenges in the world of education. For 1.5 months, students engaged in various activities such as classroom management, collaboration with supervising teachers, and group reflections. This program not only supports the development of professional skills but also shapes the attitudes and work ethics necessary for educators.